Survival of the fittest - Qamaruz Zaman, Faridah (Universiti Putra Malaysia Press, 2017)
It is the innate wisdom of nature that to continue to the next generation, a species needs to survive. Many species have adapted to their environment in various ways as illustrated in these five artefacts.